Volcanic eruption tremor from particle impacts and turbulence using conduit flow models - Katherine Coppess; Fredric Lam; Eric Dunham (Seismica)
The intensity of explosive volcanic eruptions is correlated with the amplitude of eruption tremor, a ubiquitously observed seismic signal during eruptions. Here we expand upon a recently introduced theoretical model that attributes eruption tremor to particle impacts and dynamic pressure changes in the turbulent flow above fragmentation (Gestrich et al., 2020). We replace their point source model with Rayleigh wave Green's functions with full Green's functions and account for depth variation of input fields using conduit flow models. The latter self-consistently capture covariation of input fields like particle velocity, particle volume fraction, and density. Body wave contributions become significant above 2-3 Hz, bringing the power spectral density (PSD) closer to observations. Conditions at the vent are not representative of flow throughout the tremor source region and using these values overestimates tremor amplitude. Particle size and its depth distribution alter the PSD and where dominant source contributions arise within the conduit. Solutions with decreasing mass eruption rate, representing a waning eruption, reveal a shift in the dominant tremor contribution from turbulence to particle impacts. Our work demonstrates the ability to integrate conduit flow modeling with volcano seismology studies of eruption tremor, providing an opportunity to link observations to eruptive processes.